PERBEDAAN ANTARA MEDIASI DAN KOSILIASI DALAM PENYELESAIAN SENGKETA: PERBEDAAN ANTARA MEDIASI DAN KOSILIASI DALAM PENYELESAIAN SENGKETA - Siti Aminatus Sa’diyah; Anis Fitria; Samsul Huda (JUSTNESS - Jurnal Hukun dan Agama, 2025)
Abstract Dispute resolution is an important part of maintaining order and justice in the legal system, both through litigation and non-litigation. As the public's need for faster, cheaper, and more peaceful dispute resolution grows, Alternative Dispute Resolution (ADR) methods such as mediation and conciliation are becoming increasingly relevant choices. This article aims to analyze the differences between mediation and conciliation, explain the role of the conciliator in the conciliation process, and examine the legal regulations governing both dispute resolution methods in Indonesia. This study examines the differences between mediation and conciliation in dispute resolution, the role of the conciliator in the conciliation process, and the legal regulations governing mediation and conciliation in Indonesia. This study uses a normative juridical method with a qualitative approach based on laws and legal literature. The results of the discussion show that although mediation and conciliation both involve a neutral third party and aim to reach a peaceful agreement, there are fundamental differences in the process, the role of the third party, and the level of formality. The conciliator plays a more active role than the mediator, with the authority to provide opinions and design settlement proposals, but without making binding decisions. Regulations such as Perma No. 1 of 2016, Law No. 2 of 2004, Law No. 32 of 2009, and Law No. 30 of 1999 are the legal basis that strengthens the position of mediation and conciliation as legitimate instruments in resolving various types of disputes in Indonesia. Keywords: Dispute Resolution, Mediation, Conciliation, Conciliator, Indonesian Law